Psychological interventions for the treatment of depression, anxiety, alcohol misuse or anger in armed forces veterans and their families: systematic review and meta-analysis protocol - O’Shea, Luke (Syst Rev, 2017)
BACKGROUND: Evidence highlights a high prevalence of common mental health disorders in armed forces veterans and their families, with depression, anxiety, alcohol misuse and anger being more common than PTSD. This paper presents a protocol for a systematic review and meta-analysis to identify existing randomised controlled trial (RCT) research testing the effectiveness of psychological interventions for these difficulties in armed forces veterans and their family members. METHODS: Electronic databases (CENTRAL, PsycInfo, MEDLINE, CINAHL, The Cochrane Register of Clinical Trials, EMBASE and ASSIA) will be searched to identify suitable studies for inclusion in the review supplemented by forward and backward reference checking, grey literature searches and contact with subject authors. Research including armed forces veterans and their family members will be included in the review with research including serving personnel or individuals under the age of 18 being excluded. Few RCTs examining the treatment of depression, anxiety, alcohol misuse or anger exist in armed forces veterans to date. The primary outcome will be symptomatic change following intervention for these difficulties. The secondary outcomes will include methodological aspects of interest such as discharge type and recruitment setting if data permits. In the event that the number of studies identified is too low to undertake a meta-analysis, a narrative review will be conducted. Quality assessment will be undertaken using the Cochrane Collaboration Tool and Cochran’s Q statistic calculated to test for heterogeneity as suggested by the Cochrane handbook. DISCUSSION: The review will examine the findings of existing intervention research for depression, anxiety, alcohol misuse or anger in armed forces veterans and their families, along with any effect sizes that may exist. SYSTEMATIC REVIEW REGISTRATION: PROSPERO CRD42016036676 ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13643-017-0513-8) contains supplementary material, which is available to authorized users.